An analysis of the factors affecting creative tourism and the future behavior of rural and nomadic tourists in Arasbaran region - hossein karimzade; Abolfazl Ghanbari; Samira Hashemi Amin (نشریه جغرافیا و برنامه‌ریزی, 2023)
This research has been done with practical purpose and descriptive-analytical survey method. Research data were collected by field method through questionnaire and also by archival method by referring to related documents, books and articles.The statistical population of the study includes tourists who have traveled to the target villages of tourism and nomadic areas with creative tourism potential in Arasbaran region during the summer of 1398 and 1399. To determine the sample size, Cochran's sampling formula for indeterminate communities was used.According to the obtained values, the appropriate sample size for conducting research is 384 tourists. Content validity was used to assess validity. By measuring the reliability of the questionnaire with Cronbach's alpha of 0.987, its reliability was confirmed at a high level. To measure quantitative and qualitative variables, three methods have been used: 1. Friedman test has been used to compare the means of the statistical population related to creative tourism with SPSS software. 2. For multivariate analysis of creative tourists' sense of pleasure, statistical techniques of factor analysis by using Amos Graphic 22 software have been used to determine the structural relationships between variables in the conceptual model. 3. To analyze the data related to the factors affecting the future behavior of rural and nomadic tourists, the method of minimum squares with the help of PLS software version 3 and ArcGIS software has been used to prepare the map.The results of the present study show that among the dimensions of creative rural tourism, the interaction with an average rank of 3.70 has the greatest impact on creative rural tourism. In addition, the physical and environmental dimension of pleasure with a coefficient of 1.01 has the highest coefficient among the dimensions of pleasure. The effect of factors affecting the future behavior of tourists has shown a significant relationship between research variables